Antibacterial effectiveness of moringa leaf (Moringa oleifera) nanoparticle paste with different concentration against Enterococcus faecalis: Efektivitas antibakteri pasta nanopartikel daun kelor (Moringa oleifera) dengan konsentrasi berbeda terhadap Enterococcus faecalis - Juni Jekti Nugroho; Fanny Ayu Elfira (Makassar Dental Journal, 2022)
Background: Endodontic is a treatment that aims to eliminate bacteria from the root canal system. One of the bacteria that causes root canal treatment failure is Enterococcus faecalis. Chemomechanical preparation and root canal irrigation are not sufficient to eliminate bacteria completely, so root canal medication is necessary to make it more efficient. Moringa leaves contain tannins, flavonoids and saponins which have antibacterial properties. Objective: To determine whether moringa leaf nanoparticle paste had antibacterial effectiveness against the bacterium E.faecalis. Method: Experimental laboratory with posttest with control group design with Kirby-Bauer method. The sample consisted of moringa leaf nanoparticles with concentrations of 1% and 2.5%, calcium hydroxide and aquadest with each of them being repeated 3 times. The diameter of the inhibition zone was de-termined based on the inhibitory ability of the bacteria saturated on MHA agar media. Results: the result showed that the ave-rage diameter of the inhibition zone of moringa leaf nanoparticle paste with concentrations of 1% was 8.48 mm, 2.5% was 9.17 mm and calcium hydroxide was 10.2 mm. Data processing showed that the 2.5% moringa leaf nanoparticle paste group had the same antibacterial effect as the calcium hydroxide group. Conclusion: Moringa leaf nanoparticle paste (Moringa oleifera) with concentrations of 1% and 2.5% was quite effective in inhibiting the growth of E.faecalis.